Effects of Gold Nanoparticles on Angiogenesis in A Chick Chorioallantoic Membrane Model - (:unkn) unknown (BEZMIALEM VAKIF UNIV, 2020)
Objective: Today, nanotechnology is widely used in many fields because of its ability to alter the structure of molecules at the atomic level. Metallic nanoparticles attracted great attention from researchers because of their unique properties. Based on the notable features of gold nanoparticles (AuNPs), they have long been evaluated as a potential diagnostic tool for several cancers and for drug delivery applications. Angiogenesis is the development of new vessels that support embryonic up growth and critically modulate many biological processes through adulthood. The inhibition of angiogenesis causes regression of development and metastasis of malign tumours. In this study we aim to examine the effects of AuNPs on angiogenesis in an in vivo chick chorioallantoic membrane (CAM) model. Methods: We applied 20 mL concentrations of AuNPs solution to 24 eggs of the CAM on the fifth day. After then, we evaluated results macroscopically on the 6th and 7th days. Results: In our study, we observed that AuNPs induced angiogenesis. Conclusion: We suggest that AuNPs may not be ideal nanoparticles to make biosensors due to increasing angiogenesis during the course of cancers.
Keywords: Angiogenesis; chorioallantoic membrane; gold nanoparticles; cancer; COPPER NANOPARTICLES; SIZE